Fabrications of Sb@rGO@NSC composite materials as anodes with high performance for lithium ion batteries. (1st January 2023) - Mu, Yuan; Zhang, Dakui; Li, Jianke; Han, Beibei; Xu, Guiying; Wang, Kun; An, Baigang; Ju, Dongying; Li, Lixiang; Zhou, Weimin
Abstract: In accordance with a double covering idea, the Sb@rGO@NSC (Sb covered by rGO and N, S doped carbons) with high performance is successfully synthesized by co-carbonizations using the SbCl3, GO, glucose, ammonium citrate and sulfocarbamide. The tremendous dispersions of Sb particles with nano sizes in carbon substrates and formations of 3D hierarchical porous structures make the Sb@rGO@NSC-0.3 composite material to possess the superior electrochemical performance. As can be seen, the Sb@rGO@NSC-0.3 manifests the high storage capacity (1121.2 mAh g −1 ) at 0.5 A g −1, over cycling 500 times. Concurrently, the storage capacity of Sb@rGO@NSC-0.3 has 721.1 mAh g −1 and 342.9 mAh g −1, even after carrying out the cycles 1000 times with current densities set as 1.0 A g −1 and 5.0 A g −1, respectively. The structural merits of Sb@rGO@NSC-0.3 can lead contents of Sb and contained carbons to develop their fundamental storage abilities as far as possible, which is a reason that the Sb@rGO@NSC-0.3 possesses exceedingly competitive storage performance.